Penerapan Eklesiologi Dalam 1 Petrus 2 Bagi Pembinaan Rohani Jemaat - Putra, Yulius Subari; Santo, Joseph Christ (Sekolah Tinggi Teologi Berita Hidup, 2024)
This research focuses on the application of ecclesiology in 1 Peter 2 to the spiritual formation of the church, identifying how the church's identity as a chosen nation and the holy priesthood supports a strong theological foundation in the life of the church. In this theological context, there is a gap in the understanding of the practical application of ecclesiology teachings in contemporary ecclesiastical life. The research methodology used is descriptive qualitative with descriptive analysis and exegesis approaches. The main results show that the church's identity as a chosen nation, a royal priesthood, a holy nation, and a people belonging to God strengthens the foundation of the faith of the congregation, encourages active participation in social and ecclesiastical life, and builds a strong character in the face of life's challenges. This research reveals that the integration of ecclesiology teachings in church practice can strengthen the spiritual foundation of the congregation and guide them in living their Christian vocation. The implications of this research make a significant contribution to theological literature by offering a new approach in understanding and applying ecclesiology in the spiritual development of the congregation. Penelitian ini berfokus pada penerapan eklesiologi dalam 1 Petrus 2 untuk pembinaan rohani jemaat, mengidentifikasi bagaimana identitas gereja sebagai bangsa pilihan dan imamat yang kudus mendukung fondasi teologis yang kuat dalam kehidupan jemaat. Dalam konteks teologis ini, terdapat kesenjangan dalam pemahaman aplikasi praktis ajaran eklesiologi dalam kehidupan gerejawi kontemporer. Metodologi penelitian yang digunakan adalah kualitatif deskriptif dengan pendekatan analisa deskriptif dan eksegesis. Hasil utama menunjukkan bahwa identitas gereja sebagai bangsa pilihan, imamat yang rajani, bangsa yang kudus, dan umat kepunyaan Allah memperkuat fondasi iman jemaat, mendorong partisipasi aktif dalam kehidupan sosial dan gerejawi, serta membangun karakter yang kokoh dalam menghadapi tantangan hidup. Penelitian ini mengungkapkan bahwa integrasi ajaran eklesiologi dalam praktik gereja dapat memperkuat fondasi spiritual jemaat dan membimbing mereka dalam menjalani panggilan Kristiani. Implikasi penelitian ini memberikan kontribusi signifikan terhadap literatur teologi dengan menawarkan pendekatan baru dalam memahami dan mengaplikasikan eklesiologi dalam pembinaan rohani jemaat.